Aligning top-level and domain ontologies - Schmidt, Daniela (2020)
Ontologies have been applied in diverse areas, mainly motivated by the need to represent, to share and to reuse knowledge. Top-level ontologies play a fundamental role in the construction and integration of domain ontologies, providing a well-founded reference model that can be shared across knowledge domains. Efforts in ontology matching field have been particularly dedicated to domain ontologies, however the problem of matching domain and top-level ontologies has been addressed to a lesser extent, particularly dueto their different levels of abstraction. Therefore, this work aims at filling the gap in this area. An automatic approach to align top and domain ontologies is proposed. Our approach is based on existing alignments between lexical resources and top ontologies, being used as an intermediate layer. The results was evaluated by comparing the techniques proposed in our work regarding tools developed for automatic alignment of ontologies. Although the adopted tools were not developed with a focus on aligning top and domain ontologies, they are the state of art tools in these field. The results were evaluated considering reference alignments.